WAYS TO SHAPE AND IMPROVE PERSONNEL POLICY IN ENTERPRISES (International journal of artificial intelligence, 2025)
This article considers the ways to effectively shape personnel policy in enterprises and to improve it. It emphasizes the importance of developing personnel policy on the basis of modern management principles, personnel selection, training, and incentive systems. The article is written in Uzbek and highlights modern methods of human resource management in the activity of enterprises.